2021
DOI: 10.1002/nau.24631
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of post‐radical prostatectomy urinary incontinence on everyday quality of life? Linking Pad usage and International Consultation on Incontinence Questionnaire Short‐Form (ICIQ‐SF) for a COMBined definition (PICOMB definition)

Abstract: Aims: To identify the definition for urinary continence (UC) after radical prostatectomy (RP) which reflects best patients' perception of quality of life (QoL). Methods: Continence was prospectively assessed in 634 patients, 12 months after RP using the International Consultation on Incontinence Questionnaire Short-Form (ICIQ-SF) and the number of pads employed in a 24-hour period (pad usage). We used the one-way ANOVA technique with posthoc pairwise comparisons according to Scheffé's method (homogeneous subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…As for the assessment of UC after RARP, a recent report that assessed the ICIQ‐SF score and number of pads used reported that QOL did not differ between ICIQ‐SF scores of 0 and 2 or less 22 . In this study, although the ICIQ‐SF total score was higher than the preoperative score, the median score in the NS and NNS groups at 60 months postoperatively was 2; therefore, UI may not be severe enough to impair QOL significantly.…”
Section: Discussionmentioning
confidence: 99%
“…As for the assessment of UC after RARP, a recent report that assessed the ICIQ‐SF score and number of pads used reported that QOL did not differ between ICIQ‐SF scores of 0 and 2 or less 22 . In this study, although the ICIQ‐SF total score was higher than the preoperative score, the median score in the NS and NNS groups at 60 months postoperatively was 2; therefore, UI may not be severe enough to impair QOL significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Nine (7.7%) cases of urinary retention occurred within the first postoperative day after catheter removal. Two cases required no treatment and the seven‐other resolved with urethral catheterization and a successful voiding trial within an average of 4, 5 days 1–13 . No patients had persistent high PVR volume requiring revision of the sling.…”
Section: Resultsmentioning
confidence: 96%
“…Most of them (90.4%) were expected from a normal postoperative courses or Clavien–Dindo Grade I. Five remaining cases required gamma‐aminobutyric acid analogs, 2 peripheral nerve blocks by botox injection, 2 and partial resection of the sling 1 . One patient had a urinary tract infection within the first month after implantation of the sling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations